A study on knowledge, attitude, and practice regarding biomedical waste management among health-care providers at a tertiary care hospital, Kolkata - Inba Raja Alagesan; Rajesh De; Mita Basu; Sayeli Mitra; Jadab Chandra Sardar (Indian Journal of Community and Family Medicine)
Introduction: Proper biomedical waste (BMW) disposal and its management are essential among health-care workers as it causes serious health and environmental hazards. Objectives of the study were to assess the knowledge, attitude, and practice regarding BMW management among health-care providers and to determine the factors associated with, at a tertiary care hospital in Kolkata, India. Material and Methods: A study was done among 256 health-care providers at a tertiary care hospital who were actively involved in handling BMWs. A pretested, self-administered questionnaire on knowledge, attitude, and practice regarding BMW management was used. Structured, nonparticipant observation was carried out using the Kayakalp assessment tool in the 20 BMW handling checkpoints. Statistical analysis was done using the SPSS version 20.0 (SPSS Inc., Chicago, Illinois, USA). Results: Among 256 health-care workers, 44.9% had adequate knowledge regarding BMW management and the doctors had a higher median score. 37.5% had positive attitudes and the laboratory technologists had higher median scores. 45.3% had satisfactory practice regarding BMW management and both the doctors and nurses had higher median scores. The housekeeping staff had the poorest knowledge, attitude, and practice of BMW management. Conclusion: Regular certified training among health-care staff and intense quality assessment by the waste management committee can improve BMW management overall.